2022
DOI: 10.1021/acsearthspacechem.1c00372
|View full text |Cite
|
Sign up to set email alerts
|

Transformations and Speciation of Iodine in the Environment as a Result of Oxidation by Manganese Minerals

Abstract: The fate and transport of iodine in the environment is contingent upon the presence of manganese oxides and the geochemical controls they exert. The oxidation of iodide by manganese oxides, mainly α-Mn 2 O 3 , was studied in the pH range 4−6. In the case of α-Mn 2 O 3 , the oxidation of iodide (I − ) was observed to stop at iodine (I 2 ), rather than fully oxidizing to iodate (IO 3 − ). The oxidation reaction followed an observed second order kinetics and increase of ionic strength incurred a decrease in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Both I 2 and IO − 3 adsorb to the birnessite surface. Similar results have been found over the pH range 4-6 for Mn(III) solids (Szlamkowicz et al, 2022). These MnO x reactions with Iare much slower that the reactions with reactive oxygen species (Table 2).…”
Section: Iodate Reduction By Nh 4 +supporting
confidence: 84%
“…Both I 2 and IO − 3 adsorb to the birnessite surface. Similar results have been found over the pH range 4-6 for Mn(III) solids (Szlamkowicz et al, 2022). These MnO x reactions with Iare much slower that the reactions with reactive oxygen species (Table 2).…”
Section: Iodate Reduction By Nh 4 +supporting
confidence: 84%
“…Recently, the pathway of synchronous oxidation of I − and I 2 adsorption was proposed to explain the removal of iodide by MnO 2 using experimental and theoretical methods. 11,12 Compared to iron oxides, MnO 2 exhibited a higher reactivity toward iodide oxidation in a broader pH range. Furthermore, Gallard et al revealed the formation of OICs during the oxidation of iodide by birnessite or natural manganese oxides in the presence of natural organic matter (NOM) which could be easily iodinated by in situ-formed reactive iodine (RI).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fox et al and Allard et al reported the oxidation of iodide by birnessite in the pH range of 4–8. , They revealed a two-step reaction involving the oxidation of iodide to iodine and the subsequent oxidation of I 2 intermediate (adsorbed on manganese dioxide (MnO 2 ) surface) to iodate. Recently, the pathway of synchronous oxidation of I – and I 2 adsorption was proposed to explain the removal of iodide by MnO 2 using experimental and theoretical methods. , Compared to iron oxides, MnO 2 exhibited a higher reactivity toward iodide oxidation in a broader pH range. Furthermore, Gallard et al revealed the formation of OICs during the oxidation of iodide by birnessite or natural manganese oxides in the presence of natural organic matter (NOM) which could be easily iodinated by in situ-formed reactive iodine (RI). Xu et al also found that MnO 2 enhanced the iodination of soil NOM by iodide under acidic conditions (pH 3.0–6.0) .…”
Section: Introductionmentioning
confidence: 99%
“…These remediation strategies are influenced by complex aquatic chemistry, including redox transformations that alter the mobility, bioavailability, and toxicity of radionuclides [10]. Remediation applications involving manganese oxide minerals have garnered significant attention in recent years due to their ability to sequester and facilitate the immobilization of radionuclides [11][12][13]. A reduction in highly mobile U(VI) to less soluble U(IV) species via microorganisms can result in the precipitation of U(IV) minerals, thereby limiting their migration into the environment [14].…”
Section: Introductionmentioning
confidence: 99%